2021
DOI: 10.31983/jrg.v9i1.6372
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Asupan Zat Gizi Batita Berdasarkan Tingkat Pendidikan, Status Bekerja Dan Pengetahuan Ibu

Abstract: Background: Acute malnutrition could increase mortality and morbidity indirectly in infants and toddlers. The family socio-economic characteristics including the maternal education, nutritional knowledge, and family income, are related to the incidence of stunting.Objective: To determine the relationship between maternal education, working status and knowledge on dietary intake among toddlers under 3 years old.Methods: A correlative analytic study with cross-sectional design. The populations were mothers with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…This case is in accordance with research (Chabibah, Khanifah, & Kristiyanti, 2021) that good nutritional status can be achieved if the body gets enough adequate nutrients, thus enabling physical growth, accelerating a balanced growth process for the transport of oxygen and nutrients so that cells can grow to carry out their functions normally. Therefore stunted children experience weight instability if the mother does not pay attention to the nutritional intake consumed by the child.…”
Section: Increasing Bb Of Stunted Childrensupporting
confidence: 87%
See 1 more Smart Citation
“…This case is in accordance with research (Chabibah, Khanifah, & Kristiyanti, 2021) that good nutritional status can be achieved if the body gets enough adequate nutrients, thus enabling physical growth, accelerating a balanced growth process for the transport of oxygen and nutrients so that cells can grow to carry out their functions normally. Therefore stunted children experience weight instability if the mother does not pay attention to the nutritional intake consumed by the child.…”
Section: Increasing Bb Of Stunted Childrensupporting
confidence: 87%
“…Mothers who have good knowledge tend to be 3.64 times more suitable in providing nutritional intake according to the calorie needs of toddlers. This is supported by Ni'mah's research in (Chabibah et al, 2021) which shows that only 38% of toddler mothers who experience stunting have good knowledge of toddler nutrition. This study concluded that one of the factors associated with the incidence of stunting was the mother's knowledge of toddler nutrition.…”
Section: Mother's Knowledge About Nutrition With An Increase In the W...mentioning
confidence: 80%
“…Konsumsi makanan yang tidak beragam akan berisiko kekurangan vitamin dan mineral yang akan berhubungan dengan kegagalan fungsi reproduksi. 30 Calon pengantin perlu mengonsumsi makanan beragam guna mencegah ketidaksuburan akibat asupan gizi yang kurang.…”
Section: Bahasanunclassified